2015
DOI: 10.1097/eja.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Mini-fluid challenge predicts fluid responsiveness during spontaneous breathing under spinal anaesthesia

Abstract: ΔSV100 greater than 7% accurately predicted fluid responsiveness during surgery with a grey zone ranging between 3 and 8%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 19 publications
2
38
0
1
Order By: Relevance
“…In contrast with our study, Muller et al chose colloids, which are known to increase CO more than crystalloids 19,20 , the VTI may also be more sensitive and less dependent on accuracy of arterial catheters and, much more importantly, Muller and colleagues studied patients with acute circulatory failure where all the normal cardiac reflexes may not work properly. Guinot and colleagues 21 reported a similar study using crystalloids and measuring the change in SV by thoracic impedance cardiography. A dSV of 7% after 100 mL of crystalloids showed a sensitivity of 89 %, specificity of 89 % with a negative predictive value of 93%.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast with our study, Muller et al chose colloids, which are known to increase CO more than crystalloids 19,20 , the VTI may also be more sensitive and less dependent on accuracy of arterial catheters and, much more importantly, Muller and colleagues studied patients with acute circulatory failure where all the normal cardiac reflexes may not work properly. Guinot and colleagues 21 reported a similar study using crystalloids and measuring the change in SV by thoracic impedance cardiography. A dSV of 7% after 100 mL of crystalloids showed a sensitivity of 89 %, specificity of 89 % with a negative predictive value of 93%.…”
Section: Discussionmentioning
confidence: 95%
“…More recently, smaller fluid boluses have been tested; Wu et al showed that a mini-fluid challenge of 50 ml crystalloid in mechanically ventilated critically ill patients was associated with a 17% increase in stroke volume [41]. Guinot et al demonstrated that a mini-fluid challenge of 100 ml crystalloid in spontaneously breathing patients under spinal anaesthesia 'predicted' fluid responsiveness, with a 'grey zone' ranging between 3 and 8% [54]. This could potentially decrease the cardiac filling pressures and limit the deleterious effects of fluid among nonresponders [55].…”
mentioning
confidence: 99%
“…8,25 Baseline CVP was higher in fluid non-responders, possibly indicating the presence of right ventricular dysfunction, compared to fluid responders. First, 22 controlled mechanically ventilated cardiac surgery patients with a regular heart rhythm were studied, so the results of this pilot study are certainly not generalizable to all ICU patients.…”
Section: Magder Et Al Showed That the Respiratorymentioning
confidence: 99%